Exploring the Effect of Verbal and Nonverbal Cues on Perceptions of Deception. - Henningsen, David Dryden; Valde, Kathleen S.; Davies, Elaine (Communication Quarterly, 2005)
How impressions of credibility are formed in trial type settings is examined using 173 participants. It is hypothesized that the severity of the penalty faced by an accused individual will increase participant involvement with the accused's testimony. Involvement is predicted to interact with verbal and nonverbal cues associated with deception to influence jurors' honesty judgments. Although penalty severity did not influence participant involvement, results indicate that involvement moderates the effect of verbal cues, but not nonverbal cues, on perceptions of deception. Reprinted by permission of the publisher.